Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Kinerja Karyawan Hotel Radisson Lampung - Habiburahman; Siti Nur’aini (Jurnal EMT KITA, 2023)
An employee's performance is basically the result of the employee performing his duties in accordance with the responsibilities assigned to him by the company. This is influenced by the company's remuneration and working environment, which can ultimately affect the performance of Radisson Hotels employees. The purpose of this study is to provide empirical evidence for the impact of compensation and working environment on employee performance at Radisson Hotel Lampung. The study population consisted of her 123 respondents. Based on the use of the Slovin formula for sampling, the author collected his 55 samples. The method used in this study is a quantitative method, and data analysis was performed using the validity test, reliability test, T test (partial), and F test (simultaneous) using the SPSS program. The results of this study support the hypothesis for which this study was proposed, namely that compensation has a positive and significant effect on employee performance and that work environment also has a positive and significant effect on employee performance. indicates that in addition, employee performance has a mutual influence between compensation and work environment.